A atuação do professor no processo de alfabetização de crianças com dificuldades de aprendizagem: estratégias e desafios - LOBATO, Pricila Pastana (2025)
Literacy is fundamental to educational development, and teachers play a crucial role in this process. The article seeks to meet students' individual needs and foster an inclusive learning environment, investigating effective pedagogical and didactic strategies. The research focused on analyzing teachers' practice in teaching reading and writing to children with learning difficulties, highlighting the strategies adopted and the challenges faced. Using a qualitative approach based on educational theories, the study used structured interviews as a data collection method, highlighting the interpretation of responses to evaluate the effectiveness of the implemented strategies. The results of this work provided significant insights into how teachers face and overcome challenges when teaching students with learning difficulties, in addition to identifying actions to improve teaching strategies. These findings not only promote a deeper understanding of effective educational methods in literacy, but also serve as a basis for improving future teacher training, aiming to improve the quality of education and promote a more inclusive and equitable society, where all children have equal opportunity to develop your reading and writing skills.